2005
DOI: 10.1063/1.1863449
|View full text |Cite
|
Sign up to set email alerts
|

Reversal behavior of exchange-biased submicron dots

Abstract: -Nanostructured Fe dots were prepared on antiferromagnetic FeF 2 thin films and investigated by magneto-optical Kerr effect (MOKE). We studied the influence of dot sizes on the magnetic hysteresis and compared the result with both continuous thin film bilayers and nanostructured Fe/FeF 2 pillars. Hysteresis loops were measured at temperatures below and above (10 and 90 K, respectively) the Néel temperature of the antiferromagnet. A vortex state is found for dots of 300 nm diameter, where the exchange bias fiel… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
33
1

Year Published

2005
2005
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(34 citation statements)
references
References 18 publications
0
33
1
Order By: Relevance
“…7,[22][23][24] Recently size effects involved in the EB phenomenon have been extensively studied. [25][26][27][28] This includes the dependence of the EB on the AF and FM film thicknesses as well as size effects induced by lateral structuring of the FM and AF components of EB heterostructures. Various characteristic length scales influencing the EB have been identified.…”
Section: Introductionmentioning
confidence: 99%
“…7,[22][23][24] Recently size effects involved in the EB phenomenon have been extensively studied. [25][26][27][28] This includes the dependence of the EB on the AF and FM film thicknesses as well as size effects induced by lateral structuring of the FM and AF components of EB heterostructures. Various characteristic length scales influencing the EB have been identified.…”
Section: Introductionmentioning
confidence: 99%
“…Investigations of the role of magnetic vortices in exchange bias systems have begun only recently [27][28][29][30][31]. In previous experiments, we have shown that the interplay between the unidirectional exchange bias and vortex structures can give rise to angular-dependent magnetization reversal, when the exchange bias is established with a saturated ferromagnet [27,31].…”
mentioning
confidence: 99%
“…Many models attribute this effect to the formation of domains either in the FM or in the AFM layer [14 -17]. Hence, apart from its crucial technological importance, the study of exchange bias in nanostructures is interesting from a fundamental point of view since the reduction of the lateral dimensions is likely to cause significant alterations to the domain structure of each layer [18][19][20][21][22][23][24][25].…”
mentioning
confidence: 99%